Linear T2 Hyperintensity along the Medial Margin of the Globus Pallidus in Patients with Machado-Joseph Disease and Parkinson Disease, and in Healthy Subjects - Shirai, W.; Ito, S.; Hattori, T. (American Journal of Neuroradiology, 2007)
300 Multiple ChoicesThis is a pdf-only article and there is no markup to show you.full-text.pdf